Development of HOTS (High Order Thinking Skill) Question Instrument on Thermochemistry Material - Mizzan Ayubi; Vegha Dwi Arthamena; Nurfina Aznam (Postgraduate, University of Mataram, 2023)
This study aims to make High Order Thinking Skill (HOTS) items in the form of multiple-choice types of thermochemistry material for SMA/MA. The development of the HOTS question instrument was carried out to produce valid and reliable question items. The HOTS question instrument development method uses the Mc development model. Intire. Data results in development research can be carried out using rater validation and test results. Based on the results of the rater, it can be stated that the items are feasible to test by looking at the average value of validity, which is 0.727 so that they are included in the high category by looking at aspects, namely material, construction and language aspects. Based on the calculation of the results by producing 15 questions with thermochemical material for SMA/MA which are valid with the criteria for the average level of difficulty, namely (0.584), the criteria for discriminating power of the average questions, namely (0.576) with the criteria for the average validity test, namely (0.493) reliability criteria with an average of (0.686). The conclusion obtained from the data is that the HOTS question instrument can be declared suitable for student use.